Multibody Models for the Analysis of a Fall From Height: Accident, Suicide, or Murder? - Pascoletti, Giulia; Catelani, Daniele; Conti, Paolo; Cianetti, Filippo; Zanetti, Elisabetta M. (Frontiers in Bioengineering and Biotechnology, 2019)
The final subject position is often the only evidence in the case of the fall of a human being from a given height. Foreseeing the body trajectory and the respective driving force may not be trivial due to the possibility of rotations and to an unknown initial position and momentum of the subject. This article illustrates how multibody models can be used for this aim, with specific reference to an actual case, where a worker fell into a stair well, prior to stair mounting, and he was found in an unexpected posture. The aim of the analysis was establishing if this worker was dead in that same place, if he had been pushed, and which was his initial position. A multibody model of the subject has been built (‘numerical android’), given his stature and his known mass. Multiple simulations have been performed, following a design of experiments where various initial positions and velocity as well as pushing forces have been considered, while the objective function to be minimized was the deviation of the numerical android position from the actual worker position. At the end of the analysis, it was possible to point how a very limited set of conditions could produce the given final posture, all including the application of an external pushing force (or initial speed). The full analysis gives a demonstration of the potentiality of multibody models as a tool for the analysis of falls in forensic inquiries.